GENETIC CHARACTERIZATION OF COTTON GENOTYPES BASED ON MORPHO-PHYSIOLOGICAL, BIOCHEMICAL AND DISEASE-ASSOCIATED TRAITS THROUGH MULTIVARIATE APPROACHES - HUSSAIN , S; ASLAM , MZ; QAMAR, MJ; FAROOQ , MR; MURTAZA , G; SAJJAD , M; FATIMA , NH; ZUBAIR , M; SHAH , SWH; IBRAR, I; et al. (Biological and Clinical Sciences Research Journal, 2023)
Abstract: The first step in creating new crop varieties is to evaluate current germplasm based on agro-morphological, physiological, biochemical, and molecular properties. The recent study compared the key morpho-physiological and biochemical characteristics among ten cotton genotypes. Ten cotton genotypes, including BH-249, BH-617, BH-227, BH-248, BH-613, BH-244, BH-247, BH-606, BH-184, and BH-600 were arranged in triplicates under randomized complete block design (RCBD) with plant-to-plant and bed-to-bed distances of 30 cm and 75 cm, respectively. Data obtained from the mature, fully-guarded plants were subjected to analysis of variance, and the results revealed the presence of significant variations in the studied plant traits. The correlation analysis revealed a significantly positive correlation of cotton yield with the plant height (r = 0.92**), transpiration rate (r = 0.79**), and ascorbic acid (r = 0.64**), while a significantly negative correlation with monopodial branches (r = -0.65**), virus effect plants (r = -0.59) and boll weight (r = -0.50). Similarly, seed cotton yield also showed a positive correlation with the number of bolls (r = 0.55) and peroxidase (r = 0.51), but these correlations were insignificant. Multivariate analysis approaches i.e., principal component, biplot, and cluster analysis, were used to classify and group cotton genotypes based on their performance. These analyses revealed that BH-247 and BH-606 were the most productive cotton genotypes. Therefore, these genotypes could be recommended for cultivation in core-cotton areas following extensive multilocation testing.